Analisis Hadis Aplikasi “Satu Hari Satu Hadis” pada Pusat Kajian Hadis Cinagara Bogor - Mustafa, Ilham; Arsal, Arsal; Helfi, Helfi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the hadiths in the Satu Hari Satu Hadis application developed by the Center for Hadith Studies (PKH) in Cinagara, Bogor, as a digital- based religious learning medium. Using a qualitative-descriptive approach, this research collected data through document analysis of Sahih al-Bukhari hadiths on the PKH website. The study focuses on the application and the hadiths published within the Satu Hari Satu Hadis platform. The findings show that this application provides easy access for users through hadiths from Sahih al-Bukhari, thereby ensuring the quality and credibility of the material. Features such as daily notifications and monthly themes support user consistency in studying hadith. However, limitations such as reliance on a single hadith source, the absence of contextual explanations, and the lack of interactive features remain weaknesses that need attention. Thematic messages are arranged according to the Hijri months; for example, during Rabi‘ al-Awwal, the hadiths presented consistently discuss the personality of the Prophet Muhammad. This study recommends further development through the inclusion of additional hadith sources, scholarly contextualization, and discussion features to enhance user understanding and engagement. With such innovations, the Satu Hari Satu Hadis application can become a more effective medium for hadith learning in the digital era.